Potential role of the regulatory miR1119-MYC2 module in wheat (Triticum aestivum L.) drought tolerance - Shamloo-Dashtpagerdi, Roohollah; Shahriari, Amir Ghaffar; Tahmasebi, Aminallah; Vetukuri, Ramesh R. (Frontiers in Plant Science, 2023)
MicroRNA (miRNA)-target gene modules are essential components of plants' abiotic stress signalling pathways Little is known about the drought-responsive miRNA-target modules in wheat, but systems biology approaches have enabled the prediction of these regulatory modules and systematic study of their roles in responses to abiotic stresses. Using such an approach, we sought miRNA-target module(s) that may be differentially expressed under drought and non-stressed conditions by mining Expressed Sequence Tag (EST) libraries of wheat roots and identified a strong candidate (miR1119-MYC2). We then assessed molecular and physiochemical differences between two wheat genotypes with contrasting drought tolerance in a controlled drought experiment and assessed possible relationships between their tolerance and evaluated traits. We found that the miR1119-MYC2 module significantly responds to drought stress in wheat roots. It is differentially expressed between the contrasting wheat genotypes and under drought versus non-stressed conditions. We also found significant associations between the module’s expression profiles and ABA hormone content, water relations, photosynthetic activities, H2O2 levels, plasma membrane damage, and antioxidant enzyme activities in wheat. Collectively, our results suggest that a regulatory module consisting of miR1119 and MYC2 may play an important role in wheat’s drought tolerance.